Maximizing Credit Card Customer Value - Ho, Wen Kuan (2005)
The present study present an empirical investigation of an integrated framework of customer value, customer satisfaction and behavioural outcomes by identifying the key dimensions of the credit cardholder's value, examining effects and the co-relation of customer value on customer satisfaction and in turn, the influences of customer satisfaction towards card usage and word-of-mouth in terms of the perspective of credit cardholder.